Effectiveness of Inquiry Training Model in Teaching Science at the Secondary School Level - Dwivedi, Ramesh Dhar (JOURNAL OF INDIAN EDUCATION, 2014)
This study attempts to investigate the effectiveness of Inquiry Training Model (ITM) in teaching Science at secondary school level. Four chapters of physics of class IX were taught to 50 students through ITM method and 50 students through conventional method. The two groups of students were equivalent in terms of age, sex and their previous knowledge of concepts taught (pre-test). Students were assessed using the same test after instruction (Post–test I) and retention of learned concepts was assessed after 15 days of instruction (Post-test II). Gain in achievement and retention of both the groups of students was compared using t-test and it was found that gain and retention of students receiving instruction through ITM method was more than that of the students receiving instruction through conventional method.